Modifying the critical current anisotropy of YBCO films via buffering layers on IBAD-MgO based templates - Khan MZ; Rivasto E; Wu Y; Zhao Y; Chen C; Zhu J; Palonen H; Tikkanen J; Huhtinen H; Paturi P (United Kingdom, 2022)
The role of variations in the buffer layer structure of IBAD-MgO based templates on the critical current anisotropy has been investigated in undoped and BaZrO3 (BZO) doped YBa2Cu3O6+x (YBCO) films. Not only do the natural defects grow distinct within the undoped YBCO lattice but also due to the different lengths of BZO induced nanorods within the YBCO matrix, the flux pinning properties are greatly affected by the underlying layers which in turn has a great impact on the angular dependent critical current density Jc(θ). This has been verified by transport measurements where the shape of the Jc(θ) varies in accordance with the substrates. Based on our results, the template having a cap layer with the minimum lattice mismatch and a good chemical compatibility with deposited YBCO is proven to be the best for growing both the undoped and BZO doped YBCO films. Furthermore, a model we can present based on the shapes of Jc(θ) curves depicts how the formation of nanosized defects affects the flux pinning anisotropy.
14th European Conference on Applied Superconductivity (EUCAS2019) 1-5 September 2019, Glasgow, UK